Synaptic protein deficits are associated with dementia irrespective of extreme old age - Schnaider Beeri, Michal; Haroutunian, Vahram; Schmeidler, James; Sano, Mary; Fam, Peter; Kavanaugh, Aaron; Barr, Alasdair M.; Honer, William G.; Katsel, Pavel (Neurobiology of aging, 2012)
Recent evidence shows that despite high incidence of dementia in the very old, they exhibit significantly lower levels of Alzheimer's disease (AD) neuropathology relative to younger persons with dementia. The levels and distributions of some synaptic proteins have been found to be associated with dementia severity, even in the oldest-old, but the molecular and functional nature of these deficits have not been studied in detail. The objective of this study was to assess the relationship of dementia with gene and protein expression of a panel of synaptic markers associated with different synaptic functions in young-, middle-, and oldest-old individuals. The protein and messenger RNA (mRNA) levels of 7 synaptic markers (complexin-1, complexin-2, synaptophysin, synaptobrevin, syntaxin, synaptosomal-associated protein 25 (SNAP-25), and septin-5) were compared in the brains of nondemented and demented individuals ranging from 70 to 103 years of age. One hundred eleven brains were selected to have either no significant neuropathology or only AD-associated pathology (neuritic plaques [NPs] and neurofibrillary tangles [NFTs]). The cohort was then stratified into tertiles as young-old (70–81 years old), middle-old (82–88), and oldest-old (89–103). The brains of persons with dementia evidenced significantly lower levels of gene and protein expression of synaptic markers regardless of age. Importantly, dementia was associated with reductions in all measured synaptic markers irrespective of their role(s) in synaptic function. Although other dementia-associated hallmarks of AD neuropathology (neuritic plaques and neurofibrillary tangles) become less prominent with increasing age, synaptic marker abnormalities in dementia remain constant with increasing age and may represent an independent substrate of dementia spanning all ages.